The Interaction between Bmal1 and Per2 in Mouse BMSC Osteogenic Differentiation - Haiya Zhuo; Yuhong Wang; Qing Zhao (Stem Cells International)
The circadian clock is a system that controls endogenous time of organisms, and it regulates the physiology and behavior of bodies. The transcription factors Brain and Muscle ARNT-like Protein 1 (BMAL1) and Period2 (Per2) are components of the circadian clock, and they play vital roles in circadian clock function. Both Bmal1−/− mice and Per2−/− mice display obvious bone volume changes. In this study, we inhibited the expression of Bmal1 in bone marrow-derived mesenchymal stem cells (BMSCs) using a lentiviral vector harboring RNAi sequences, which increased the osteogenic differentiation capability of BMSCs. We also suppressed Per2 gene expression using an adenovirus vector harboring RNAi sequences, and similarly, the osteogenic differentiation ability of BMSCs was enhanced. Furthermore, when both Bmal1 and Per2 gene expression was suppressed in BMSCs by lentiviral and adenoviral interference, the osteogenic differentiation capability was stronger than that in BMSCs following single-gene inhibition. Our data support that both Bmal1 and Per2 play negative roles in BMSC osteogenic differentiation and that Bmal1 and Per2 have a synergistic effect on the osteogenic differentiation of BMSCs.